Causes and Consequences of Flavivirus RNA Methylation - Bradrick, Shelton S. (Frontiers in Microbiology, 2017)
Mosquito-borne flaviviruses are important human pathogens that represent global threats to human health. The genomes of these positive-strand RNA viruses have been shown to be substrates of both viral and cellular methyltransferases. N7-methylation of the 5′ cap structure is essential for infection whereas 2′-O-methylation of the penultimate nucleotide is required for evasion of host innate immunity. N6-methylation of internal adenosine nucleotides has also been shown to impact flavivirus infection. Here, I summarize recent progress made in understanding roles for methylation in the flavivirus life-cycle and discuss relevant emerging hypotheses.